If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5.26s + -2.01 = -8.94 Reorder the terms: -2.01 + 5.26s = -8.94 Solving -2.01 + 5.26s = -8.94 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '2.01' to each side of the equation. -2.01 + 2.01 + 5.26s = -8.94 + 2.01 Combine like terms: -2.01 + 2.01 = 0.00 0.00 + 5.26s = -8.94 + 2.01 5.26s = -8.94 + 2.01 Combine like terms: -8.94 + 2.01 = -6.93 5.26s = -6.93 Divide each side by '5.26'. s = -1.317490494 Simplifying s = -1.317490494
| -2g+7= | | -9s+18-18=18s-4-2 | | 7v+224=-84v | | 3v+9+v=2v-2+3 | | -38-37= | | 10+5x-x=10+4x+4 | | 45=26+b | | X+2+x-10=90 | | 2v+1=-3v+8v+10 | | 6u-12+2=6u-10 | | 14m-2m-2m-8m=12 | | 45=26 | | h=2*3.14*30.25+2*3.14*5.5*18.7 | | 3y+6-y=2y-2+10 | | 729/1.000 | | 6x+12=3x-9 | | 14g-13g=17 | | -2x-4+7=3x+18 | | 4x-2(x-2)=-5+4x-3 | | 3w+6+w=4w-4+10 | | 1-4n= | | -1/16a=0 | | h=2*3.14*r^2+2*3.14*r*h | | 10g-5g=20 | | 6(.3x+2)+3x=x+60 | | 8t-6t=6 | | -13+-7=4 | | 6(2a+10)=-3a+25+8a | | 0.9=4.5 | | (1/9)^(-3/2) | | 10a-8a=14 | | l+15.2=-4.7 |